Effects of Weizhuan’an on rats with precancerous lesions of gastric cancer based on regulating gastric mucosal microflora and inflammatory factors - Lu, Yuting; Liu, Huayi; Shang, Jiaju; Mao, Yijia; Meng, Lingkai; Gao, Changbai (Frontiers in Pharmacology, 2024)
Objectives This study aimed to observe the intervention of Weizhuan’an prescription on rats with precancerous lesions of gastric cancer (PLGC) as well as its regulation on gastric mucosal microflora and inflammatory factors and explore the pharmacodynamic mechanisms of Weizhuan’an Formula. Methods The rats were classified into the blank control group (BCG); low-, medium-, and high-dose groups of Weizhuan’an prescription (LDG, MDG, and HDG, respectively); and natural recovery group (NRG) at random. The rats in the traditional Chinese medicine (TCM) group were given corresponding doses of Weizhuan’an formula, while the rats in the NRG and BCG were given an equivalent volume of distilled water for 12 weeks. After that, gastric mucosa samples of rats were collected to observe the general and pathological changes in the gastric mucosa; the changes in gastric mucosal microflora were detected by 16S rDNA amplicon sequencing, and the inflammatory factors were analyzed by cytokine antibody microarray and Western blotting. Results The results suggest that compared with the BCG, the pathology of gastric mucosa and gastric mucosal microflora and inflammatory factors in rats with PLGC have changed significantly, while Weizhuan’an formula effectively improved them, especially in the MDG and HDG (p < 0.05). Compared with the NRG, the abundance of probiotics such as Lactobacillus and Veillonella were increased, while the abundance of pathogens such as Proteobacteria and Pseudomonas was decreased (p < 0.05, p < 0.01), and the relative contents of IL-2, IL-4, IL-13, and MCP-1 in gastric mucosa were decreased (p < 0.05). Moreover, it can upregulate the DNA-binding transcriptional regulator, ABC type multidrug transport system, and related enzymes and affect the signaling pathways such as viral protein interaction with cytokine and cytokine receptor and T cell receptor signaling pathway significantly (p < 0.05, p < 0.01), which can promote drug absorption and utilization and repair damaged gastric mucosa. Conclusion The study confirmed that Weizhuan’an prescription can treat rats with PLGC by regulating gastric mucosal microflora and inflammatory factors.